The role of politics in the construction of a capable bureaucracy - Malale, Ishmael (Graduate School of Development Policy and Practice, 2017)
This research explores the role of politics in the construction of a capable bureaucracy. The dominant discourse deals with the structural attributes of a developmental state, and eschews the inherent politics of the construction or emergence of bureaucracy in a state. The focus of the research is about how capable bureaucracies emerge out of an abidingly complex and messy political reality. This research endeavours to unravel the complex, dynamic, often messy inherent intersection of politics and bureaucracy. It is argued that politics are an inherent ingredient of the fermentation of a capable bureaucracy, in which the agency of political actors is critical and that public reforms often spawn from particular critical junctures. This research undertakes a comparative study of South Korea, Unites States of America and South Africa, and juxtaposing the first two comparators with South Africa in order to draw important lessons for the latter. The endeavour looks at the pre-history, critical junctures, and the moment of consolidation to demonstrate how history shapes and influences the institutional realities of different countries; examine the proximate events or driving forces that contribute to or precipitated the emergence of capable bureaucracies in the successful comparators and distill lessons for South Africa. In the United States of America public service reforms fostered by broad coalitions in collaboration with political actors eradicated patronage and ensured economic progress. In South Korea the symbiotic relationship of meritocratic bureaucracy with an uncorrupt political elite ensured high speed growth. The research strives to demonstrate that building a capable bureaucracy is not a straightforward affair - exposing the nature of challenges and complexities of setting up a capable bureaucracy, thus contributing to the discourse - grappling with constructing a capable bureaucracy in South Africa.